Efficacy of air polishing in comparison with hand instruments and/or power-driven instruments in supportive periodontal therapy and implant maintenance: a systematic review and meta-analysis - Shiuan Lee Tan; Galvinderjeet Kaur Grewal; Nor Shafina Mohamed Nazari; Tuti Ningseh Mohd-Dom; Nor Adinar Baharuddin (BMC Oral Health, 2022)
Abstract Background Supportive periodontal therapy (SPT) is the key for a stable periodontal health following active treatment. Likewise, implant maintenance is crucial following implant placement. This systematic review aimed to assess clinical outcomes, patients’ perception, and cost-effectiveness of repeated periodontal therapy with air polishing devices (APDs) in comparison with hand instruments and/or power-driven instruments (conventional interventions) in SPT and implant maintenance. Methods Electronic search for randomised controlled clinical trials with minimum 6 months follow-up for SPT and implant maintenance programme was conducted for data published from 01 January 2000 to 30 April 2020 using multiple databases and hand searching. Risk of bias was assessed using the Revised Cochrane Risk-of-Bias tool (RoB 2). Results A total of 823 articles were screened. 4 SPT and 2 implant maintenance studies were eligible for inclusion. For SPT, repeated APDs interventions revealed no statistically significant difference when compared to the conventional interventions (weighted mean difference [WMD] 0.11 mm, p = 0.08). Likewise, no statistical difference was noted in terms of percentage of bleeding on probing (BOP) and clinical attachment level (CAL) gain. APDs were associated with lower pain score (based on Visual Analogue Scale) and higher patient acceptance in SPT studies. For implant maintenance, APDs resulted in reduction in PPD and percentage of BOP. However, CAL gain was comparable between the two groups. In terms of patient reported outcomes, no implant maintenance studies recorded any forms of patient reported outcomes. In addition, no studies reported on economic evaluation of APDs in both SPT and implant maintenance. Conclusion Within the limitations of this systematic review and meta-analysis, repeated subgingival debridement using APDs in SPT resulted in similar clinical outcomes but better patients’ comfort when compared to the conventional interventions. For implant maintenance, there is limited evidence to show that repeated application of APDs leads to improved clinical outcomes when compared to conventional treatments.